Analysis Of Sexual Dimorphism In Morphometric Variables Of Cane Rat (2018)
The sex effect and interrelationship between body weight and six linear body measurements o fforty-five (15 bucks and 30 does) grasscutters aged between 12 and 24 months was assessedusing path analysis. Body weighty and linear body measurements: hind leg length, rump height, paunch girth, face width, mouth width, and total body length were measured for the male and female grass cutter. Results showed that there were significant differences (p<0.05) between the male and the female cane rats for all the parameters measured indicating sexual dimorphism in the cane rat All parameters assessed had highly significant (p<0.0001) and very strong positive correlation coefficients in both sexes. The path analysis indicated that in males, hindleg length (2.86;p<0.0001) had the highest direct effect on body weight, while rump height (-1.45; p<0.0001), had a negative direct effect In the female group, all the parameters evaluated had a nonsignificant, positive direct effect The hind leg length was observed to have the highest (0.29; p<0.0001) path coefficient while the mouth width (0.02; p<0.0001) had the least path coefficient It was concluded that sex had an effect on the interrelationship between body weight and linear body measurements in grasscutter.